Pengendalian Biaya Kedelai Home Industry Tahu-Tempe Mbak Sri - Valentina Monoarfa; Nur Khairunnisa Ahmad; Pindrawaty Mooduto (ManBiz: Journal of Management and Business, 2024)
This study aims to analyze the material cost control in Mbak Sri's home industry of tofu and tempeh production. Material costs constitute a significant portion of the total production costs, and effective control measures are crucial for ensuring profitability. The research employs a qualitative approach, utilizing observation and in-depth interviews to gather data. The findings reveal that Mbak Sri implements several cost control strategies, including careful material selection, efficient utilization, and waste minimization. However, challenges arise due to fluctuating raw material prices and limited bargaining power. The study recommends implementing a comprehensive material management system, establishing strategic supplier relationships, and exploring alternative sourcing options to enhance cost control measures. By addressing these recommendations, Mbak Sri's home industry can improve its overall operational efficiency and profitability.